PENERAPAN METODE ORDINARY KRIGING PADA PENDUGAAN KADAR NO2 DI UDARA (Studi Kasus: Pencemaran Udara di Kota Semarang) - Gera Rozalia; Hasbi Yasin; Dwi Ispriyanti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Air pollution must be addressed. Nitrogen Dioxide is one of the important factors in air pollution. To determine concentration level of the pollutant “Badan Lingkungan Hidup Kota Semarang” already take measurements at several points. However, because of blocked considerable cost, is not much point to do measurements. In this study, will be used Ordinary Kriging method to estimate at some points in Semarang. In this methode will compare the value of the eksperimental semivariogram with some theoretical semivariogram models (spherical, eksponensial, and gaussian) to get the best model that will be used in the estimation. In this study, estimate the concentration of Nitrogen Dioxide in the air in a number of village in Semarang. Based on analysis we found the best model is spherical model with Nitrogen Dioxide produces estimates is the highest in Sub Gebangsari and Nitrogen Dioxide lowest in Sub Patemon. Keywords: Ordinary Kriging, Semivariogram, Nitrogen Dioxide.